Dietary supplementation with algae-based ingredients modulates antioxidant defenses and immune response in sea urchin Paracentrotus lividus following a Vibrio parahaemolyticus challenge - Ana Filipa Rodrigues; S. Lourenço; A.S. Gomes; M. Vaz; H. Cardoso; A.P. Violante; T. Baptista (Animal Feed Science and Technology, 2026)

Inclusion of microalga Dunaliella salina in the diet of laying hens: effects on egg quality and sensory traits - Obete Madacussengua; Cátia Falcão Martins; Ana Beatriz Rodrigues Tavares; Daniela Filipa Pires Carvalho; Ana Rita Mendes; Tiago Guerra; António Pagarete; Suzana Ferreira-Dias; Miguel Pedro Mourato; José António Mestre Prates; André Martinho de Almeida; Madalena Lordelo (Algal Research, 2026)

Diel activity guild drives different mammal responses to fragmentation and degradation in the Amazon deforestation arc - Luan G. A. Goebel; Ana Filipa Palmeirim; Juliano A. Bogoni; Gabriela Rodrigues Longo; Ana Catarina Araújo-Fernandes; Eder Correa Fermiano; Manoel dos Santos-Filho (Biodiversity and Conservation, 2026)
Fragmentation and degradation have profound effects on species’ habitat use and activity patterns. According to their diel activity guild, species may respond differently to environmental change, with diurnal species expected to be more vulnerable to these changes. Here, we test this hypothesis by investigating how fragmentation, and degradation modulate the habitat use and overlap in diel activity of contrasting mammal diel activity guilds in the Amazonian arc of deforestation. We used data from camera-traps (2,970 trap-days) across 30 forest fragments (from 8 to 435 ha) and three continuous forest sites. Considering diurnal and nocturnal mammals separately, we examine (1) the effects of fragmentation, and degradation on the habitat use and (2) the overlap in their diel activity across the different forest sizes. Habitat use by diurnal mammals increased with forest size, but not that of nocturnal species. In general, diurnal mammals anticipate their peak activity from 00:00 h to 6:00 h into smaller fragments (

Article Title: Impact of Dysphagia on Quality of Life in Machado-Joseph Disease - Joana Paz Mota; Inês Tello Rodrigues; Ana Filipa Ferreira; Ana Rosa Vieira Melo; Paula Pires; Pedro Lopes; João Vasconcelos; Mafalda Raposo; Manuela Lima (The Cerebellum, 2025)

Phytochemical diversity and biological activities of Hypericum japonicum and Hypericum sampsonii: potential for natural product-based food applications - Paula Barciela; Daniele B. Rodrigues; Ana Perez-Vazquez; Tayse F.F. da Silveira; Tânia C.S.P. Pires; Filipa Mandim; Maria Carpena; Carla Pereira; Isabel C.F.R. Ferreira; Lillian Barros; Miguel A. Prieto (Food Chemistry, 2025)

Multi-faceted decline of vertebrate diversity in an endemism zone of the Brazilian Amazon - Luan Gabriel Araujo Goebel; Juliano A. Bogoni; Gabriela Rodrigues Longo; Ana Filipa Palmeirim; Eder Correa Fermiano; Dionei José da Silva; Áurea Regina Alves Ignácio; Manoel dos Santos-Filho (Journal for Nature Conservation, 2025)

Patterns and Drivers of Taxonomic and Functional Change in Large Oceanic Island Bird Assemblages - Filipa C. Soares; Ricardo F. de Lima; Ana S. L. Rodrigues; Pedro Cardoso; Thomas J. Matthews; Jorge M. Palmeirim (Global Ecology and Biogeography, 2024)
Aim We map global patterns of taxonomic and functional change between past (pre‐human impacts) and present (after anthropogenic extinctions and introductions) in large oceanic island bird assemblages and investigate if these patterns can be explained by island characteristics and anthropogenic factors. Location Sixty‐four oceanic islands (>100 km 2 ). Time Period Late Holocene. Major Taxa Studied Terrestrial and freshwater bird species. Methods We compiled information on extinct, extant native and introduced bird species for all islands and used a probabilistic hypervolume approach to build a multi‐dimensional trait space and calculate several functional diversity metrics before and after extinctions and introductions. We identified which islands are global hotspots of human‐induced transformation by mapping multiple facets of biotic change and investigated intrinsic island characteristics and anthropogenic factors as drivers for these observed patterns. Results The Hawaiian and Mascarene islands stand out as hotspots of taxonomic and functional change, but all islands changed taxonomically and functionally, mostly gaining species but losing functional richness. Taxonomic and functional changes vary across islands but are often consistent within the same archipelago. Island isolation and surface can explain some of the observed variations, but anthropogenic factors, namely human occupation, also shaped both taxonomic and functional changes. Islands with higher human pressure, as well as larger islands with high elevation ranges, tended to have greater losses in functional richness. Main Conclusions Most biodiversity change assessments are still largely based exclusively on taxonomic diversity, which is particularly worrying in the case of oceanic islands given that the magnitude of functional diversity change is often considerably larger. We call for comprehensive assessments of changes in both taxonomic and functional diversity across oceanic islands in order to better understand the drivers of these changes and, in turn, predict future trends.

Effect of solid-state fermentation of Brewer's spent grain on digestibility and digestive function of european seabass (Dicentrarchus labrax) juveniles - Tássia Estevão-Rodrigues; Helena Fernandes; Sara Moutinho; Diogo Filipe; Filipa Fontinha; Rui Magalhães; Ana Couto; Marta Ferreira; Margarida Gamboa; Carolina Castro; Isabel Belo; José Salgado; et al. (Animal Feed Science and Technology, 2024)

Ultrasound-assisted extraction of bioactive compounds from goji berries: Optimization, bioactivity, and intestinal permeability assessment - Filipa Teixeira; Ana Margarida Silva; Stefania Sut; Stefano Dall'Acqua; Oscar L. Ramos; Alessandra B. Ribeiro; Ricardo Ferraz; Cristina Delerue-Matos; Francisca Rodrigues (Food Research International, 2024)

Combined effects of bird extinctions and introductions in oceanic islands: Decreased functional diversity despite increased species richness - Filipa C. Soares; Ricardo F. de Lima; Jorge M. Palmeirim; Pedro Cardoso; Ana S. L. Rodrigues (Global Ecology and Biogeography, 2022)
Aim We analyse the consequences of species extinctions and introductions on the functional diversity and composition of island bird assemblages. Specifically, we ask if introduced species have compensated the functional loss resulting from species extinctions. Location Seventy‐four oceanic islands (> 100 km 2 ) in the Atlantic, Pacific and Indian Oceans. Time period Late Holocene. Major taxa studied Terrestrial and freshwater bird species. Methods We compiled a species list per island (extinct and extant, native and introduced), and then compiled traits per species. We used single‐trait analyses to assess the effects of past species extinctions and introductions on functional composition. Then, we used probabilistic hypervolumes in trait space to calculate functional richness and evenness of original versus present avifaunas of each island (and net change), and to estimate how functionally unique are extinct and introduced species on each island. Results The net effects of extinctions and introductions were: an increase in average species richness per island (alpha diversity), yet a decline in diversity across all islands (gamma diversity); an average increase in the prevalence of most functional traits, yet an average decline in functional richness and evenness, associated with the fact that extinct species were functionally more unique (when compared to extant natives) than introduced species. Main conclusions Introduced species are on average offsetting (and even surpassing) the losses of extinct species per island in terms of species richness, and they are increasing the prevalence of most functional traits. However, they are not compensating for the loss of functional richness due to extinctions. Current island bird assemblages are becoming functionally poorer, having lost unique species and being composed of functionally more redundant species. This is likely to have cascading repercussions on the functioning of island ecosystems. We highlight that taxonomic and functional biodiversity should be assessed simultaneously to understand the global impacts of human activities.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Retina and Brain Display Early and Differential Molecular and Cellular Changes in the 3xTg-AD Mouse Model of Alzheimer’s Disease - Ana Catarina Rodrigues-Neves; Rafael Carecho; Sónia Catarina Correia; Cristina Carvalho; Elisa Julião Campos; Filipa Isabel Baptista; Paula Isabel Moreira; António Francisco Ambrósio (Molecular Neurobiology, 2021)

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Year-Long Rhinovirus Infection is Influenced by Atmospheric Conditions, Outdoor Air Virus Presence, and Immune System-Related Genetic Polymorphisms - Ana Filipa Rodrigues; Ana Mafalda Santos; Ana Maria Ferreira; Roberta Marino; Maria Esmeralda Barreira; José Manuel Cabeda (Food and Environmental Virology, 2019)

The Retina as a Window or Mirror of the Brain Changes Detected in Alzheimer’s Disease: Critical Aspects to Unravel - Samuel Chiquita; Ana C. Rodrigues-Neves; Filipa I. Baptista; Rafael Carecho; Paula I. Moreira; Miguel Castelo-Branco; António F. Ambrósio (Molecular Neurobiology, 2019)

Unravelling the antitumoral potential of novel bis(thiosemicarbazonato) Zn(II) complexes: structural and cellular studies - Elisa Palma; Hugo M. Botelho; Goreti Ribeiro Morais; Inês Rodrigues; Isabel Cordeiro Santos; Maria Paula Cabral Campello; Paula Raposinho; Ana Belchior; Susana Sousa Gomes; Maria Fátima Araújo; Isabel Correia; Nadia Ribeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2019)

Tauroursodeoxycholic Acid Enhances Mitochondrial Biogenesis, Neural Stem Cell Pool, and Early Neurogenesis in Adult Rats - Rita Soares; Filipa F. Ribeiro; Sara Xapelli; Tânia Genebra; Maria F. Ribeiro; Ana M. Sebastião; Cecília M. P. Rodrigues; Susana Solá (Molecular Neurobiology, 2017)